PENGARUH PENDIDIKAN KEWIRAUSAHAAN MELALUI VARIABEL INTERVENING TEORI PERILAKU TERENCANA TERHADAP INTENSI BERWIRAUSAHA MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER - Cahyono, Arie Eko (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
This study aimed to examine the effect of entrepreneurship education on entrepreneurial intentions of students through the theory of planned behavior approach. Is entrepreneurship attitude, subjective norm, and behavioral control as an intervening entrepreneurship education on entrepreneurial intentions of students. Research carried out a quantitative study. The population in this study is the S1 class of 2011 students in the Faculty of Teacher Training and Education Jember University academic year 2013/2014 with a total sample of 240 people. The method of analysis using Structural Equation Modeling (SEM). The results showed that entrepreneurship education has an influence on entrepreneurial attitudes and control student behavior, but does not affect the subjective norm. While the effect to the intention to come by that intention is influenced by subjective norms and behavioral control, while the attitude of no effect to the intention. As for the indirect effect is found that entrepreneurship education affects entrepreneurial intentions through behavior control, while that through entrepreneurship attitude and subjective norm indirectly no effect